The effect of the COVID-19 pandemic on the mental and emotional health of athletes - Jia, L.; Carter, M. V.; Cusano, A.; Li, X.; Kelly, J. D.; Bartley, J. D.; Parisien, R. L. (The American Journal of Sports Medicine, 2023)
Background: The coronavirus disease 2019 (COVID-19) pandemic has caused the cancellation or postponement of virtually every sporting event, resulting in training disruptions, income loss, and career uncertainties for athletes around the world. At present, the effect of the COVID-19 pandemic on the mental and emotional health of athletes is not well understood.